The role of the marine research infrastructures in the European marine observation landscape: present and future perspectives - Dañobeitia, Juan José; Pouliquen, Sylvie; Pade, Nicolas; Arvanitidis, Christos; Sanders, Richard; Stanica, Adrian; Gourcuff, Claire; Petihakis, George; Tegas, Valentina; Favali, Paolo (Frontiers in Marine Science, 2023)
The ocean regulates the exchange, storage of carbon dioxide, plays a key role in global control of Earth climate and life, absorbs most of the heat excess from greenhouse gas emissions and provides a remarkable number of resources for the human being. Most of the geo-hazards occur in oceanic areas. Thus, high-quality systematic observations are necessary tools for improving our understanding, and subsequent assimilation to provide early warning systems. A holistic scientific approach for the understanding of the ocean’s interrelated processes requires coordinated and complementary monitoring and observation programmes. Research Infrastructures (RIs) are large-scale facilities that provide resources and services for the scientific communities to conduct high-level research and foster innovation. RIs benefit from strong governance and multi-annual funding from their member states with operational life spans in decades. RIs promote knowledge, outreach and education to public, private, and policy stakeholders, and they play a key role in enabling and developing research in all scientific domains and currently represent a growing share of coordinated investment in research, and also in providing essential observations to operational services such as Copernicus. They are strategically important for Europe to lead a global movement towards a data-driven, interconnected, open digital twin that brings together different disciplines, clean technologies, public and private sectors and a broad scientific/technological community, as well as education and training. In Europe several marine RIs have been established, which are maintained by national and European Union (EU) resources. The aims of these infrastructures are aligned with the key priorities of the UN Decade of Ocean Science for Sustainable Development; and with the new European Research Area (ERA) Policy Agenda annexed to the Council conclusions on the ERA governance1, which set out 20 concrete actions for 2022-2024 to contribute to the priority areas defined in the EU Pact for R&I2. The purpose of this paper is to demonstrate that the combined expertise and assets of Europe’s marine RIs can form a comprehensive and holistic framework for long-term, sustainable integrated marine observation. Through this integration process the marine RIs can become better and better a significant pillar of the European Ocean Observing System (EOOS). Such a framework must be built as part of interfaces of interaction and promote not only scientific excellence but also innovation at all levels.